If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -12) = -8x + -30 Reorder the terms: -2(-12 + x) = -8x + -30 (-12 * -2 + x * -2) = -8x + -30 (24 + -2x) = -8x + -30 Reorder the terms: 24 + -2x = -30 + -8x Solving 24 + -2x = -30 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 24 + -2x + 8x = -30 + -8x + 8x Combine like terms: -2x + 8x = 6x 24 + 6x = -30 + -8x + 8x Combine like terms: -8x + 8x = 0 24 + 6x = -30 + 0 24 + 6x = -30 Add '-24' to each side of the equation. 24 + -24 + 6x = -30 + -24 Combine like terms: 24 + -24 = 0 0 + 6x = -30 + -24 6x = -30 + -24 Combine like terms: -30 + -24 = -54 6x = -54 Divide each side by '6'. x = -9 Simplifying x = -9
| -3x+6=-6x-24 | | 2x*4y=16 | | -2(x+12)=-8x+30 | | -2x-9=-5x+24 | | 1=10-3v | | -2x+9=-5x+24 | | 6x*2=48 | | 16-2g=10 | | (x+(2+i))(x-(2-i))=0 | | 18 = h3+ 15 | | 3x+2y=y-4+5x-y | | 5x^2+y^2=1 | | 32x-12=-18 | | X+3=5+4 | | ln(3x+1)=-4 | | 27000*x-0,5=10000*x | | 14(X)+48(1-X)=47.5 | | 78(X)+47(1-X)=47.7 | | 16y-20=60-4y | | 0.4x+16.5=x-1.62 | | X=Z-(X*Y) | | x=(x-1)(1.075) | | 9x+2y=192 | | 2x^2+4x+21=0 | | x^2+25x-259=0 | | 10x+8=8x+2 | | 9x+9=9x+1 | | 20x+9=7x+1 | | 2/3j=-12 | | 3/4j=-12 | | 3x+2=1x+7 | | 14x+1=4x+2 |